AN IN-DEPTH ANALYSIS ON ERRORS OF INDONESIAN STUDENTS WITH LOW PROFICIENT LEVEL IN PRONOUNCING CONSONANT ENGLISH PHONEMES - Thamrin, Sri Wahyuni; Nurbiati, Nurbiati; Abrar, Andi Eritme Yustika; Marzuki, Mutmainnah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This study aims to determine the pronunciation errors of phonemes produced by students of Muhammadiyah University of Bulukumba. This study applies a qualitative paradigm. The subjects of this study were second semester students of the Department of English Education with low proficiency levels at the University of Muhammadiyah Bulukumba. Students were asked to pronounce 24 consonant sounds at the beginning, middle, and end of the word to find the data. Students' pronunciation was then phonologically analyzed based on the classification of pronunciation errors found by Moulton, W. G. (1962).The results shows that errors in the pronunciation of English consonants are found in stop voicess, fricative, africative, nasal and semi-vowel consonants. The types of errors in the pronunciation of consonant phonemes are allophones, phonemics and phonetics errors. Allophone error is found in the stop voiceless consonants /p/, /t/, and /k/ which were found at the beginning of the syllable. Phonemic and phonetic errors are found in the pronunciation of voiced /v/, voiced /z/, voiceless /θ/, voiced /ð/, and voiceless /ʃ/. The same error is also found in voiceless /ʃ/ which was pronounced without using the sound /h/, as well as phonetic errors that was pronounced using the sound /t/. Phonetic errors are also found in the pronunciation of fricative sounds /tʃ/ and /dᴣ/, nasal /ƞ/ and semi vowel sounds /j/ which were pronounced not in accordance with the actual sound, thus other meaningless sounds are formed.